Non-pharmacological Interventions for Wound-related Pain in Chronic Lower Limb Ulcers: A Systematic Review - Azka Qothrunnadaa; Tintin Sukartini; Ika Nur Pratiwi (Universitas Pahlawan Tuanku Tambusai, 2025)
Chronic lower extremity wounds impose significant physical, emotional, and socioeconomic burdens, with pain being a prevalent yet often neglected symptom. This systematic review examined the effectiveness of non-pharmacological interventions for wound-related pain in adults with chronic lower limb ulcers. A PRISMA-guided search was conducted across Scopus, PubMed, Web of Science, and ProQuest, including randomized controlled trials (RCTs) and quasi-experimental studies. Twelve RCTs published between 2011 and 2025 involving 1,078 participants were analyzed. Interventions ranged from single-session methods to multi-session therapies, behavioral programs, and modality-based treatments. Findings showed that stress balls and cold saline significantly reduced procedural pain, while electrical stimulation and motivational support provided sustained benefits. In contrast, virtual reality and heated saline offered limited pain relief but improved patient comfort. Overall, simple, low-cost approaches demonstrated promise for immediate relief, whereas structured behavioral and modality-based therapies supported longer-term pain management. These strategies, being safe and feasible, may complement standard wound care, particularly within nursing practice. Further high-quality, large-scale trials are warranted to refine their clinical application.